Changes in white matter as determinant of global functional decline in older independent outpatients: three year follow-up of LADIS (leukoaraiosis and disability) study cohort. (6th July 2009) - Inzitari, Domenico; Pracucci, Giovanni; Poggesi, Anna; Carlucci, Giovanna; Barkhof, Frederik; Chabriat, Hugues; Erkinjuntti, Timo; Fazekas, Franz; Ferro, José M; Hennerici, Michael; Langhorne, Peter; O'Brien, John; et al.
Abstract : Objective To assess the impairment in daily living activities in older people with age related changes in white matter according to the severity of these changes. Design Observational data collection and follow-up of a cohort of older people undergoing brain magnetic resonance imaging after non-disabling complaints. Setting 11 European centres. Participants 639 non-disabled older patients (mean age 74.1 (SD 5.0), 45.1% men) in whom brain magnetic resonance imaging showed mild, moderate, or severe age related changes in white matter (Fazekas scale). Magnetic resonance imaging assessment also included cerebral infarcts and atrophy. Main outcome measure Transition from no disability (defined as a score of 0 or 1 on the instrumental activities of daily living scale) to disability (score ≥2) or death over three year follow-up. Secondary outcomes were incident dementia and stroke. Results Over a mean follow-up period of 2.42 years (SD 0.97, median 2.94 years), information on the main outcome was available for 633 patients. The annual rate of transition or death was 10.5%, 15.1%, and 29.5%, respectively, for patients with mild, moderate, or severe age related changes in white matter (Kaplan-Meier log rank test P<0.001). In a Cox model comparing severe with mild changes and adjusted for clinical factors of functional decline, the risk of transition to disability or death was more than twofold higher (hazard ratio 2.36, 95% confidence interval 1.65 to 3.81). The other predictors were age group, history of atrial fibrillation, and complaint of gait disturbances. The effect of severe changes remained significant independently of baseline degree of atrophy and number of infarcts. Incident stroke and dementia only slightly modified this effect. Conclusion The three year results of the LADIS study suggest that in older adults who seek medical attention for non-disabling complaints, severe age related changes in white matter independently and strongly predict rapid global functional decline.